2014
DOI: 10.1039/c4cp00367e
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular gel from folic acid with multiple responsiveness, rapid self-recovery and orthogonal self-assemblies

Abstract: Through a good/poor solvent strategy, native folic acid (FA) which behaves as a super-gelator in DMSO-water system can be successfully employed to construct supramolecular gels. The system exhibited morphological evolution with the increase of FA concentration; various phases such as vesicles, fiber/vesicles, fiber/nanoparticles, nanoparticles were probed. In the self-assembly process, l-glutamic acid moiety induced the formation of helical 1-dimensional (1-D) fibers which further self-assembled into a gel. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 98 publications
2
52
0
Order By: Relevance
“…) and gelator concentration. [10,34] The Fmoc-Glu gel displays a shrinking trend, and the G N values are thus changeable ( Figure 2). After adding Mm, with increasing gelator concentrations (molar Fmoc-Glu/Mm 1/1), G N shows an increasing trend (Figure 3 d).…”
Section: Self-assembly Behavior Of Fmoc-glu/mm Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…) and gelator concentration. [10,34] The Fmoc-Glu gel displays a shrinking trend, and the G N values are thus changeable ( Figure 2). After adding Mm, with increasing gelator concentrations (molar Fmoc-Glu/Mm 1/1), G N shows an increasing trend (Figure 3 d).…”
Section: Self-assembly Behavior Of Fmoc-glu/mm Complexmentioning
confidence: 99%
“…For instance, graphene can be stabilized in solvents by covalent modification to graphene oxide [7] or polymer-grafted graphene, [8] and surfactants and compounds with large p-conjugated surfaces improve the solubility of graphene in a noncovalent manner. [9] Supramolecular materials formed from building blocks that are held together noncovalently are of vital importance in materials science, because their dynamic nature endows them with particular features such as self-healing, [10] stimuli responsiveness, [11] and shape memory. [12] Among them, supramolecular gels constituted by low molecular weight gelators through noncovalent interactions such as H-bonds, solvophobic forces, donor-acceptor interactions, and p-p stacking are an important category of soft materials.…”
Section: Introductionmentioning
confidence: 99%
“…Suitably disposed donor‐acceptor sites in pterin skeleton drive hydrogen bond‐assisted self‐recognition event, in a manner analogous to guanine tetramer formation, and it is shown that the presence of monovalent cations imparts stability to cholesteric phases. A recent study demonstrated that a change in monovalent cations resulted in enhanced FA tetramer rigidity, as a result of favorable stacking interactions and tetrad elongation .…”
Section: Introductionmentioning
confidence: 99%
“…Introduction 10 Supramolecular chemistry and molecular self-assembly have 11 been widely used to fabricate various functional new materials [1-12 8]. For example, supramolecular gels (SGs) obtained from low-13 molecular-weight gelators via non-covalent interactions have 14 received considerable attention because of their potential applica- 15 tions in drug delivery and chemical sensor [9][10][11][12][13][14][15][16][17][18][19][20][21]. The application 16 of gels is dependent on their mechanical properties in a great 17 extent.…”
mentioning
confidence: 99%